PENGARUH LIKUIDITAS, UKURAN PERUSAHAAN, PROFITABILITAS DAN PERTUMBUHAN ASET TERHADAP STRUKTUR MODAL (STUDI EMPIRIS PERUSAHAAN ADVERTISING, PRINTING DAN MEDIA YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2017-2019) - Rahayu, Ema Lukyta; Hartono, Arif; Ulfah, Ika Farida (Jurnal Ekonomi Syariah Darussalam, 2021)
This study aims to examine the effect of liquidity, firm size, profitability, and asset growth to the capital structure. The data in this test is data from 2017-2019. The subjects in this study are Advertising, Printing, and Media companies listed on the Indonesia Stock Exchange since 2017 or earlier until 2019. Supposed on the result of partially testing are Liquidity, Company Size, and Asset Growth influence the capital structure. Whereas the Profitability are not influence the capital structure. And if the result of simoultaneously testing, Liquidity, Company Size, Profitability, and Asset Growth influence the capital structure.